2021
DOI: 10.3390/ijerph181910194
|View full text |Cite
|
Sign up to set email alerts
|

Healthy-Canteen Displays: A Tactic to Encourage Community Sport Canteens to Provide Healthier Food and Beverage Options

Abstract: (1) Background: Community sport settings present a range of conflicting health behaviours, including the tension between being physically active and consuming discretionary foods. Therefore, community sport settings are considered a promising location for health promotion. The aim of this project was to evaluate perceptions, knowledge and the impact (e.g., barriers and outcomes) of a healthy-canteen (cafeteria) display, based on traffic light labeling (TLL), which was set up at an Australian Basketball Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Education and support for training and competition venues to provide non-UPF options may lead to enhanced access to these foods where they are most convenient to athletes. Other research has demonstrated that healthy canteen displays at sporting association trade shows can support organisations to plan and implement changes in their canteens ( 47 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Education and support for training and competition venues to provide non-UPF options may lead to enhanced access to these foods where they are most convenient to athletes. Other research has demonstrated that healthy canteen displays at sporting association trade shows can support organisations to plan and implement changes in their canteens ( 47 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Innovative study designs are required to address both of these limitations, especially when evaluating the effectiveness of policies in changing overall consumption patterns, and estimating effects on health [ 37 ]. Additionally, studies investigating healthy food and drink initiative implementation often report concerns of increased costs to retailers [ 38 , 39 ]. Despite this, changes to food and operational costs as a result of improving the healthiness of items for sale, and how food costs can be optimised to increase the likelihood of switches to healthier menus being profitable, have not been investigated.…”
Section: Discussionmentioning
confidence: 99%